Strength training. Preventing hamstring injuries in the sprinter - Cissik, J. M. (Techniques Magazine, 2012)
For sprinters to be able to perform, they have to be healthy. One of the most common and devastating injuries for sprinters is a hamstring injury. Not only can these impact performance and training, but they can also continue to plague athletes long after the initial injury occurs. This article is going to take a brief look at the anatomy of the hamstrings and their function during sprinting, and then present exercises to help prevent hamstring injuries.